2022
DOI: 10.1039/d2cc00768a
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium complexes with N-heterocyclic vinylidene ligands

Abstract: Vanadium complexes with N-heterocyclic vinylidene ligands are reported. The vinylidenes can act as 6e− donor ligands, leading to strong metal–carbon interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…Inspired by the reaction of the imidazole‐based diazoolefin IDipp=CN 2 [30] with VCl 3 (THF) 3 which resulted in the formation of a vinylidene complex, [31] we investigated the reaction of complex 1 with IDipp=CN 2 targeting the synthesis of a thorium vinylidene. Addition of one equivalent IDipp=CN 2 to a Et 2 O solution of 1 at −40 °C and the reaction mixture was warmed to room temperature for 3 h resulting in an orange reaction mixture and full consumption of the starting material (Figure S33).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the reaction of the imidazole‐based diazoolefin IDipp=CN 2 [30] with VCl 3 (THF) 3 which resulted in the formation of a vinylidene complex, [31] we investigated the reaction of complex 1 with IDipp=CN 2 targeting the synthesis of a thorium vinylidene. Addition of one equivalent IDipp=CN 2 to a Et 2 O solution of 1 at −40 °C and the reaction mixture was warmed to room temperature for 3 h resulting in an orange reaction mixture and full consumption of the starting material (Figure S33).…”
Section: Resultsmentioning
confidence: 99%
“…[28e,29] In an effort to find new routes to actinide alkylidenes, Hayton and co-workers explored the reactivity of diphenylcyclopropene with actinides and reported that ring opening of a thorium cyclopropenyl complex generates a transient thorium carbene that could not be isolated. [28e] Inspired by the reaction of the imidazole-based diazoolefin IDipp = CN 2 [30] with VCl 3 (THF) 3 which resulted in the formation of a vinylidene complex, [31] we investigated the reaction of complex 1 with IDipp = CN 2 targeting the synthesis of a thorium vinylidene. Addition of one equivalent IDipp = CN 2 to a Et 2 O solution of 1 at À 40 °C and the reaction mixture was warmed to room temperature for 3 h resulting in an orange reaction mixture and full consumption of the starting material (Figure S33).…”
Section: Reaction With An Imidazole-based Diazoolefinmentioning
confidence: 99%
“…The synthesis of such N‐heterocyclic diazoolefins can be achieved by reaction of the corresponding N‐heterocyclic olefins [13] with nitrous oxide [14] . N‐Heterocyclic diazoolefins can act as C‐donor ligands to metal complexes, [11, 12] and it has been shown for vanadium complexes that N 2 loss can lead to the formation of alkenylidene ligands [15] …”
Section: Methodsmentioning
confidence: 99%
“…[14] N-Heterocyclic diazoolefins can act as C-donor ligands to metal complexes, [11,12] and it has been shown for vanadium complexes that N 2 loss can lead to the formation of alkenylidene ligands. [15] The reaction of [Cu(COD)Cl] 2 (COD = 1,5-cyclooctadiene) with two equivalents of diazoolefin 1 [11b] resulted in the formation of the adduct 2, which could be isolated in 70 % yield (Scheme 2). Utilization of the ionic complex [Cu(CH 3 CN) 4 ](BF 4 ) instead of [Cu(COD)Cl] 2 gave the homoleptic complex 3 in 94 % yield.…”
mentioning
confidence: 99%